Todo pasa: Escritos de prensa 1964 - 1980 de Horacio Serrano (Colección Arte y Cultura, 2016)
Between 1963 and 1980, Horacio Serrano published nearly a thousand articles and columns in the newspaper El Mercurio. This selection rescues the main thematic axes of those writings: Chile and the Chileans, the classic cultural legacy, oriental wisdom, our confused and incipient modernization and the world of women and feelings. To read Horacio Serrano is to recover part of our landscape and is to ask ourselves again about Chilean identity. His columns continue to challenge today's readers, due to their originality, due to his ability to join current events with the most permanent cultural debate and the details of daily life with the most important dilemmas of the spirit.